2017
DOI: 10.1371/journal.pcbi.1005537
|View full text |Cite
|
Sign up to set email alerts
|

An independent component analysis confounding factor correction framework for identifying broad impact expression quantitative trait loci

Abstract: Genome-wide expression Quantitative Trait Loci (eQTL) studies in humans have provided numerous insights into the genetics of both gene expression and complex diseases. While the majority of eQTL identified in genome-wide analyses impact a single gene, eQTL that impact many genes are particularly valuable for network modeling and disease analysis. To enable the identification of such broad impact eQTL, we introduce CONFETI: Confounding Factor Estimation Through Independent component analysis. CONFETI is designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 105 publications
(124 reference statements)
0
17
0
Order By: Relevance
“…Besides the aforementioned methods, there are other methods that can be applied at the joint modeling stage, giving the users freedom to select the method that best suits their needs, for example, Listgarten et al (2010);Fusi et al (2012); Velu and Reinsel (2013); Gao et al (2014);Ju al. (2017); etc.…”
Section: Joint Modelingmentioning
confidence: 99%
“…Besides the aforementioned methods, there are other methods that can be applied at the joint modeling stage, giving the users freedom to select the method that best suits their needs, for example, Listgarten et al (2010);Fusi et al (2012); Velu and Reinsel (2013); Gao et al (2014);Ju al. (2017); etc.…”
Section: Joint Modelingmentioning
confidence: 99%
“…Each dataset underwent the same preliminary preprocessing including TMM normalization, gene-level filtering, and gene outlier removal. We applied six data correction procedures to each dataset: 1) no correction, 2) known covariate adjustment, 3) probabilistic estimation of expression residuals (PEER)(1), 4) confounding factor estimation through independent component analysis (CONFETI)(12), 5) removal of unwanted variation (RUVCorr)(7), or 6) principal component adjustment (PC)(13). RUVCorr, CONFETI, and PC adjustment are three alternative data correction approaches designed to identify and remove hidden confounds while retaining patterns of coexpression in the dataset.…”
Section: Resultsmentioning
confidence: 99%
“…For each dataset we adjusted for the number of PEER factors selected to optimize cis-eGene discovery in the latest quantitative trait locus study by the GTEx Consortium(3): 15 factors for tissues with < 150 samples, 30 factors for tissues with 150-249 samples, 45 factors for tissues with 250-349 samples, and 60 factors for tissues with ≥ 350 samples. CONFETI: Confounding Factor Estimation Through Independent component analysis (CONFETI) is designed to adjust for non-genetic confounding factors while retaining genetically-regulated coexpression (i.e. broad impact eQTL) in the expression dataset(12). Briefly, factors are derived from the full gene expression dataset using independent component analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spurious eQTLs easily result from microarray expression data because confounding effects are induced by various measurement errors ( Churchill, 2002 ; Akey et al, 2007 ). Mixed model analyses, such as the intersample correlation emended method ( Kang et al, 2008 ), probabilistic analysis of genomic data ( Fusi et al, 2012 ), and confounding factor estimation through independent component analysis ( Ju et al, 2017 ), have been suggested to correct for the confounding effects. These analytical models incorporate random effects with an intersample covariance structure that might explain unknown confounding factors produced by measurement errors.…”
Section: Issues With Analytical Modelsmentioning
confidence: 99%